2005
DOI: 10.1186/1471-2229-5-s1-s22
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione-dependent formaldehyde dehydrogenase/GSNO reductase from Arabidopsis.Expression pattern and functional implications in phytoremediation and pathogenesis

Abstract: The glutathione-dependent formaldehyde dehydrogenase (FALDH) is the main enzyme of the formaldehyde detoxification system in eukaryotes. In Arabidopsis FALDH is coded by a single gene, which is constitutively expressed [1]. By immunolocalization experiments on Arabidopsis root and leaf sections, we demonstrate that the pattern of expression of the enzyme is cell specific. By using tobacco BY-2 cell cultures we show that FALDH co-localizes with tubulin on the cortical microtubules and the microtubules figures (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Hence, we assumed that the GSNOR expression levels do not change due to the Sb stress. In fact, in other studies, authors reported expression in GSNOR in plants free of any stress (Airaki et al [ 107 ], in C. annum ; Martínez et al [ 108 ], in Arabidopsis; or Kubienová et al [ 109 ] and Jahnová et al [ 110 ], in tomato). GSNOR can be regulated at both transcriptional and post-translational levels.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we assumed that the GSNOR expression levels do not change due to the Sb stress. In fact, in other studies, authors reported expression in GSNOR in plants free of any stress (Airaki et al [ 107 ], in C. annum ; Martínez et al [ 108 ], in Arabidopsis; or Kubienová et al [ 109 ] and Jahnová et al [ 110 ], in tomato). GSNOR can be regulated at both transcriptional and post-translational levels.…”
Section: Discussionmentioning
confidence: 99%